EFFICACY AND SAFETY OF INTERLOCKED INTRAMEDULLARY NAILING FOR OPEN FRACTURE SHAFT OF TIBIA - Ahmed, Naveed; Khan, Muhammad Shoaib; Afridi, Sikandar Aziz; Awan, Abdus Saboor; Afridi, Shamshad Khan; Sultan, Shahid; Saifullah, Khalid; Lodhi, Fahad Saqib (Journal of Ayub Medical College Abbottabad, 2016)
Background: Due to increasing population and changing human habits the number of accidents and high energy trauma is rising. Management of open fracture tibia is a complex problem and is a challenge for both orthopaedic and plastic surgeons. The study was carried out to ascertain the efficacy and safety of interlocked intra-medullary nailing for open shaft tibial fractures in patients presenting at or after 24hr of injury. Methods: In this descriptive case series, over a period of 6 moths, 163 consecutive cases of open fracture of tibial shaft were reviewed in terms of clinical profile, time of presentation, and gender distribution. Results: In this study mean age was 30±0.02 years. Males comprised 85% of study population while 15% were females. Gustilo-I type fracture and Gustilo-II type fracture was diagnosed in 90% and 10% patients respectively. Thirty three percent patients had wound infection while fracture union was found in 15% cases. Moreover interlocked intramedullary nailing for open fracture shaft of tibia was safe in 80% patients while this procedure was effective in 85%. Conclusion: Un-reamed, interlocked intra-medullary nailing may be considered as a suitable option for treatment of open fractures of tibia. Keywords: Tibia, intramedullary nailing, open fractures shaft